2014
DOI: 10.1103/physrevstab.17.041004
|View full text |Cite
|
Sign up to set email alerts
|

Beam-beam effects investigation and parameters optimization for a circulare+ecollider at very high energies

Abstract: Several proposals exist for future circular electron-positron colliders designed for precise measurements of the Higgs boson characteristics and electroweak processes. At very high energies, synchrotron radiation of the particles in a strong electromagnetic field of the oncoming bunch (beamstrahlung) becomes extremely important, because of degradation of the beam lifetime and luminosity. We present theoretical calculations of beamstrahlung (including the beam lifetime reduction and the energy spread increase) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 5 publications
0
34
0
Order By: Relevance
“…On the one hand, the numerical simulations have clearly demonstrated that the crab waist scheme works well even if the beam collisions take place inside the experimental detector with a strong solenoidal field. This is important for promoting studies of future electronpositron colliders based on the crab waist collisions scheme, FCC-ee crab waist option, for example [18]. On the other Comparison between the machine normalized background hitting the KLOE-2 calorimeter in the region around the electron beam exit as a function of instantaneous luminosity (left) and KLOE-2 normalized trigger level (right) for the previous (black dots) and the current (red squares) electron machine working point.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the numerical simulations have clearly demonstrated that the crab waist scheme works well even if the beam collisions take place inside the experimental detector with a strong solenoidal field. This is important for promoting studies of future electronpositron colliders based on the crab waist collisions scheme, FCC-ee crab waist option, for example [18]. On the other Comparison between the machine normalized background hitting the KLOE-2 calorimeter in the region around the electron beam exit as a function of instantaneous luminosity (left) and KLOE-2 normalized trigger level (right) for the previous (black dots) and the current (red squares) electron machine working point.…”
Section: Discussionmentioning
confidence: 99%
“…The beamstrahlung limit [6] is due to the fact that at high energies and luminosities, beamstrahlung, the synchrotron radiation emitted by an incoming electron in the collective electromagnetic field of the opposite bunch at an interaction point, reduces beam lifetimes to values where the top-up injector cannot cope. The effect of beamstrahlung is very implementation specific and can be mitigated by small vertical emittance and large momentum acceptance.…”
Section: The Beamstrahlung Limitmentioning
confidence: 99%
“…FCC-ee M. Koratzinos 6 The only method that can provide the accuracy needed is the so-called resonant depolarization technique [15], each measurement of which has an instantaneous accuracy of O (10 -6 ). It is based on the fact that the spin of an electron in a storage ring (in a perfectly planar machine and in the absence of solenoids) will precess times for one revolution, where is the anomalous magnetic moment and the Lorenz factor of the electron and therefore the spin tune is 440.6486 1…”
Section: Pos(eps-hep2015)518 Pos(eps-hep2015)518mentioning
confidence: 99%
“…Figure 10 displays the expected luminosity per IP as a function of c.m. energy, assuming crab-waist collisions [32] at two IPs. The anticipated luminosity performance has been confirmed by beam-beam simulations [37,38].…”
Section: Future Hadron Colllidermentioning
confidence: 99%